2014
DOI: 10.1590/0074-0276130558
|View full text |Cite
|
Sign up to set email alerts
|

Malaria in the state of Rio de Janeiro, Brazil, an Atlantic Forest area: an assessment using the health surveillance service

Abstract: The lethality of malaria in the extra-Amazonian region is more than 70 times higher than in Amazonia itself. Recently, several studies have shown that autochthonous malaria is not a rare event in the Brazilian southeastern states in the Atlantic Forest biome. Information about autochthonous malaria in the state of Rio de Janeiro (RJ) is scarce. This study aims to assess malaria cases reported to the Health Surveillance System of the State of Rio de Janeiro between 2000-2010. An average of 90 cases per year had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 25 publications
2
18
0
2
Order By: Relevance
“…Although, malaria was endemic throughout the country in the past, in the Atlantic coastline region, where 70% of the country's population is concentrated, locally transmitted malaria now correspond to less than 0.5% of total extra-Amazonian incidence, because almost all cases are actually imported from the Amazon, where only 13% of the population has settled. 57 Local transmission in the Atlantic Forest region may therefore be considered as a very rare occurrence, although A. darlingi has been retrieved throughout the entire region and presumed responsible for the few outbreaks that have occurred. 58 Increased A. darlingi human-biting activity was reported in areas of the Iquitos-Nauta road that have undergone deforestation, which was interpreted as implying that deforestation was a causal factor for A. darlingi presence and malaria risk.…”
mentioning
confidence: 99%
“…Although, malaria was endemic throughout the country in the past, in the Atlantic coastline region, where 70% of the country's population is concentrated, locally transmitted malaria now correspond to less than 0.5% of total extra-Amazonian incidence, because almost all cases are actually imported from the Amazon, where only 13% of the population has settled. 57 Local transmission in the Atlantic Forest region may therefore be considered as a very rare occurrence, although A. darlingi has been retrieved throughout the entire region and presumed responsible for the few outbreaks that have occurred. 58 Increased A. darlingi human-biting activity was reported in areas of the Iquitos-Nauta road that have undergone deforestation, which was interpreted as implying that deforestation was a causal factor for A. darlingi presence and malaria risk.…”
mentioning
confidence: 99%
“…We observed no human malaria symptomatic cases and all thick and thin blood smears were negative for Plasmodium species. These results are not unexpected because data from the governmental surveillance system have demonstrated that cases occur throughout the year, with an annual average of 4 or fewer cases across the state particularly during the warmer season 7,23 . Interestingly, malaria outbreaks associated with P. simium occurred in areas close to the municipality of Guapimirim in the summers of 2015 and 2016 9 .…”
Section: Discussionmentioning
confidence: 77%
“…darlingi now rarely found in this area 5 . In recent years, a new malaria epidemiological scenario is emerging in Rio de Janeiro, with the presence of cases imported from endemic areas of Brazil and outside the country and occasional autochthonous cases including outbreaks 6,7,8,9 . In 2016, the World Health Organization (WHO) launched the "Global Technical Strategy for Malaria 2016-2030", with the goal of "preventing a resurgence of malaria in all countries and areas that are malaria-free" 10 .…”
Section: Introductionmentioning
confidence: 99%
“…aquasalis, que tem mantido a introdução de casos esporádicos de malária e surtos (Revisão em Pina- . Entre 2002 e 2010 foram notificados 808 casos, sendo 35 autóctones (Miguel et al, 2014).…”
Section: Malária Na Região Extra-amazônicaunclassified
“…Entre 2006-2008, três casos diagnosticados como P. vivax, pela GE e PCR, com sintomas leves e parasitemia baixa, eram de localidades situadas entre os municípios de Nova Friburgo e Guapimirim na "Serra dos Órgãos", na região da Mata Atlântica (Revisão em Oliveira-Ferreira et al, 2010). Além disso, dos 35 casos autóctones ocorridos no estado entre 2002 e 2010, sete foram no Município do Rio de Janeiro, um em Campos dos Goytacazes e um em Petrópolis (Miguel et al, 2014).…”
Section: Repetitividadeunclassified